Agricultural activities during October - Sepat, Seema (Indian Farming, 2020)
THE October month is the most important for agricultural activities. In this month, most of the kharif crops are ready to harvest. Meanwhile, sowing of rabi crops also starts in the rainfed regions. The timely sowing of rabi crop is important to utilize the stored soil moisture in rainfed regions. The sowing of chickpea, lentil and oilseed crop such as mustard and among the food grain crops, wheat and rabi maize starts in this month. Spring sugarcane can be sown in this month for higher profits. The harvesting of kharif rice is done in this month. Therefore, in this article, agricultural activity need to be done during October month has been described in detail.